TWO NONLINEAR MATHEMATICAL MODELS TO ESTIMATE THE INTENSITY-DURATION-RETURN PERIOD OF RAINFALL EVENTS - Pereyra-Díaz, D (Ecosistemas y Recursos Agropecuarios, 2014)
In developing countries, many hydraulic engineering projects for the planning, designing, operation and protection against oods use intense rainfall data to estimate maximum runo. In the case of Mexico, the only available rainfall data are usually those recorded with a pluviometer over 24 hours. The scarcity of data makes it necessary to validate and implement models to estimate short duration intense rainfall data. Two nonlinear mathematical models that estimate rainfall intensity based on the duration of the storm and the return period are proposed in this study. The models were adjusted to short duration rainfall data for the city of Xalapa (Veracruz), Cañon Fernández (Durango) and Cazadero (Zacatecas), and were compared with other models reported in the literature. The results show that: a) for model I, the determination coecient (R2) varied from 0.927 to 0.932 and the standard error of estimation (Re) from 6.7 to 9.4 mm h-1, and b) for model II, the R2 varied from 0.934 to 0.988 and the Re from 3.5 to 6.5 mm h-1. The fit shows that model II is better than model I. In comparison, complex models like those of Koutsoyiannis et al. (1998), Chow et al. (1994) and Sherman (1931) were adjusted to extreme rainfall data for the city of Xalapa.